JUMLAH DENSITAS LARVA DAN PUPA NYAMUK AEDES AEGYPTI DI DESA BEBEL DI KECAMATAN WONOKERTO - Nila Oktaviani; Wiwik Dian Cahyani (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Climate change may affect the migration, breeding, behavior, maturity rate, the length of life of the mosquito A. aegypti (Georgina, 1999; in Lembaga Ilmu Pengetahuan Indonesia, 2006); and such other mosquito vector populations A. aegypti at any time can change the density, increased fecunditas and high fertility, as well as a short generation time (Regis, et al., 2008). The material research is the mosquito A. aegypti larvae and pupa stage in the homes and surrounding areas. The tools used are termohigrometer used to measure temperature and humidity. Conducted a survey research methods. Based on the stratification of endemicity, the sampling is stratified random sampling. The sample was taken at random as many as 100 homes and set as the point of sampling, analyse the regresi multivariat, at level signifikan 0,05. Based on the description above, it can be concluded that the  most influential environmental factors on the density of  the mosquito A. aegypti larvae and pupae on stage at the Village Bebel is the temperature and humidity (P <0.05), respectively accounted for 44.8%  and  39.9%.  Based  on  the conclusions obtained  by the strategy to  lower levels  of density-stage larvae and pupae of mosquitoes A. aegypti, when an increase in temperature and humidity can be used as a benchmark to begin cleaning the environment.Keyword : Larvae, Pupa, Aedes aegypti, Temperature, Humidity